Faktor Kunci dalam Mengembangkan Kewirausahaan Hijau Generasi Z Muslim - Noor, Sufiana; Rahmawati, Fitri (Universitas Islam Raden Rahmat, 2024)
This research aims to test and analyses the influence of Entrepreneurial Education, Entrepreneurial Self-Efficacy, and Entrepreneurial Attitude on Green Entrepreneurial Intention among Muslim Gen Z in Kudus Regency. The type of research used is field research with a quantitative approach. The sample for this research was 233 respondents using a purposive sampling. Analysis was carried out by SPSS 23. The result shows Entrepreneurial Education, Entrepreneurial Self-Efficacy, and Entrepreneurial Attitude have positive influences on the Green Entrepreneurial Intention of Muslim Gen Z. This study suggests that future research could explore how to further integrate Islamic values and mentorship programs to support Muslim Gen Z's green entrepreneurial aspirations.